Estimating the Size of the Shadow Economy: Methods, Problems and Open Questions - Friedrich Schneider; Andreas Bühn (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper presents the various methods to estimate the size of the shadow economy, their strengths and weaknesses. The purpose of the paper is twofold. Firstly, it demonstrates that no ideal method to estimate the size and development of the shadow economy exists. Because of its flexibility, the MIMIC method used to get macro-estimates of the size of the shadow economy is discussed in greater detail. Secondly, the paper focuses on the definition and causal factors of the shadow economy as well as on a comparison of the size of the shadow economy using different estimation methods.
Keywords: D78; E26; H20; H11; H26; K42; O50; O17; 330; shadow economy estimates; MIMIC approach; methods to estimate the shadow economy; advantages and disadvantages of the measurement methods